(3TQM GdQSGdI GdhdOjI aj GdBOGHs - (3eLghds
(3ChdgG (B:s
(3bhdg HSe Gddg YOd Yf GdWQjb GdeTghQ QYGjI dUfYI GdGSJZQGH Ch JfHjgG Ydi Cf COGA GdhGLH jMUd HCj WQjb cGf Ch ddGNJUGQ EP g CNUQ ef GdWQjb GdeTghQ GdHGA ddGSJYGfI eJYdb HaYd ebOQ (B...s
(3BNQgG (B:s
(3aYdjg Cf jfXQ aj QSGdJfG hCf jQLY di QSGdJfG GdeYehdI Cj GdeDdaI dJbQjQ bhGfjf GdefGXQI hjLH Ydi GdeSJajOjf ef GdeYdejf hGdeJYdejf CMSf Gddg JYGdi LedI eYJQVI OYGFjI JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdadSaI hGdefWbs